Forecasting Zones of Air Pollution from Solid Waste Landfills - Medvedieva, O. O.; Dziuba, S. V.; Biliaiev, M. M.; Kozachyna, V. A.; Kirichenko, P. S. (Science and Transport Progress, 2025)
Purpose. The work is aimed at developing a mathematical model that allows to quickly calculate the area of chemical air pollution during the emission of hazardous substances from solid waste landfills. The mathematical model takes into account meteorological parameters, geometric shape of the landfill, intensity of emission of hazardous substances from the landfill. Methodology. The two-dimensional equation of convective diffusion transfer of a conservative impurity from the atmosphere is used to analyze the intensity and size of chemical air pollution during the emission of hazardous substances from the landfill. A difference scheme of splitting is used to numerically solve the equation of convective-diffusive transfer of an impurity. The emission of hazardous substances from the landfill is modeled using the Dirac delta function. Findings. The developed mathematical model takes into account the main physical factors that affect the process of dispersion of hazardous substances from the landfill. On the basis of the developed numerical model, a computational experiment was conducted to assess the impact of the landfill on the environment. Originality. On the basis of the developed numerical model, a computer code was developed that allows predicting chemical pollution of the atmospheric wind and the underlying surface in the event of emission of hazardous substances from the surface of a solid waste landfill. The developed model and computer code make it possible to quickly assess the extent and intensity of environmental pollution from landfills, which is important when selecting sites for new or reconstructed landfills. Practical value. The software implementation of the developed numerical model was carried out, and a computational experiment was conducted to illustrate the effectiveness of using the model to solve applied problems related to the impact of landfills on the environment. The results of the numerical experiment are presented.